Malaysian Market Model for Palm Oil: Some Policy Simulations - Lubis, Abdul Rahman (1994)
Malaysian palm oil market is vulnerable to the market variables and policy instruments. This study is undertaken to model Malaysian palm oil market and evaluate the impact of the market variables and policy instruments on Malaysian palm oil market. Eleven structural equations and six identities are specified and identified. The structural equations are estimated by means of the two-stage least square with principal component employed in the first stage regression. The effects of variations in the market variables and policy instruments on Malaysian palm oil market are obtained by simulating the market models and by deducting the simulated values from the base solutions. The results show that estate production is determined by production lagged one period, current price, domestic price lagged four to six periods and rubber price. The adjustment coefficient of estate production is low at 0.2834. The price elasticity of estate supply is inelastic at 0.1721. Smallholder production is influenced by production lagged one period, domestic price lagged five and six periods and re-planting grant. The price elasticity of supply for smallholder and its adjustment coefficient are inelastic at 0.0577 and low at 0.1924 respectively. Domestic demand is determined by the price of groundnut oil, Malaysian industrial production index and domestic demand lagged one period. The elasticities of domestic demand with respect to own price and substitute prices are inelastic. The adjustment coefficient of domestic demand is also low at 0.4872. Except for the United States and the rest of EEE, price of Malaysian palm oil in the world market is an important determinant of Malaysian palm oil export to the importing countries. Export of Malaysian palm oil is also influenced by prices of its substitutes, industrial production index in each country and lagged of one period of its export. The elasticities of the export demand to all of the countries with respect to own price and its substitute prices are inelastic. The main determinants influencing Malaysian palm oil price in the world market are world consumption of palm oil and lagged one period of Malaysian palm oil price in the world market rubber price. The adjustment coefficient of estate production is low at 0.2834. The price elasticity of estate supply is inelastic at 0.1721. Smallholder production is influenced by production lagged one period, domestic price lagged five and six periods and re-planting grant. The price elasticity of supply for smallholder and its adjustment coefficient are inelastic at 0.0577 and low at 0.1924 respectively. Domestic demand is determined by the price of groundnut oil, Malaysian industrial production index and domestic demand lagged one period. The elasticities of domestic demand with respect to own price and substitute prices are inelastic. The adjustment coefficient of domestic demand is also low at 0.4872. Except for the United States and the rest of EEe, price of Malaysian palm oil in the world market is an important determinant of Malaysian palm oil export to the importing countries. Export of Malaysian palm oil is also influenced by prices of its substitutes, industrial production index in each country and lagged of one period of its export. The elasticities of the export demand to all of the countries with respect to own price and its substitute prices are inelastic. The main determinants influencing Malaysian palm oil price in the world market are world consumption of palm oil and lagged one period of Malaysian palm oil price in the world market